Regulators of commensal and pathogenic life‐styles of an opportunistic fungus—Candida albicans. Issue 4 (23rd February 2021) - Rai, Laxmi Shanker; Wijlick, Lasse Van; Bougnoux, Marie‐Elisabeth; Bachellier‐Bassi, Sophie; d'Enfert, Christophe
Abstract: The yeast Candida albicans is primarily a commensal of humans that colonizes the mucosal surfaces of the gastrointestinal and genital tracts. Yet, C. albicans can under certain circumstances undergo a shift from commensalism to pathogenicity. This transition is governed by fungal factors such as morphological transitions, environmental cues for instance relationships with gut microbiota and the host immune system. C. albicans utilizes distinct sets of regulatory programs to colonize or infect its host and to evade the host defense systems. Moreover, an orchestrated iron acquisition mechanism operates to adapt to specific niches with variable iron availability. Studies on regulatory networks and morphogenesis of these two distinct modes of C. albicans growth, suggest that both yeast and hyphal forms exist in both growth patterns and the regulatory circuits are inter‐connected. Here, we summarize current knowledge about C. albicans commensal‐to‐pathogen shift, its regulatory elements and their contribution to human disease. Take aways: Both yeast and hyphal cell co‐exist during commensal and pathogenic growth of C. albicans . Hyphal‐specific virulence factors decide the shift from commensal to pathogenic growth of C. albicans . An integrated regulatory circuit of C. albicans commensalism and pathogenicity evolved to respond to niche‐specific signals. Abstract : Transcriptional regulators of commensalism and virulence of Candida albicans . A summary of C. albicans transcription regulators which have been identified to participate in commensal life (blue), virulence (red) or both (black), and their functions in the cell.